Poços de Caldas – Cabo Frio Alignment: a Petrochronological Review of an Unconventional Plume Model - Maia Teodoro, Marco Aurélio (2025)
This work reviews the Poços de Caldas – Cabo Frio Alignment (PCCFA), one of Brazil's alkaline igneous provinces, comprising syenites, phonolites, and trachytes, as well as magmatic breccias. TAS and Harker (for major and trace elements) diagrams suggest two groups based on the silica content. From the TAS diagram, it is noted that the less evolved rocks plot mainly in the tephrite/basanite and foidite fields, while the more evolved rocks predominantly fall in the phonolite and trachyte fields. In the Harker diagrams, correlations with silica can be observed for some oxides/elements, such as TiO2, CaO, Rb, Sr, Zr, Y, and Nb. From the normalized diagrams, it is evident that the less evolved rocks exhibit low variability, indicating similar sources and petrogenetic processes. In contrast, the more evolved ones present several anomalies (Ba, Sr, Ti, Rb, Zr, and Eu), suggesting different mineral fractionations. In addition, a wide range of normalized values is observed for certain elements, such as Ba, Sr, and Pb, which may indicate distinct evolutionary processes. Sr and Nd isotopic data show show similar trends, suggesting a mixture of DMM and EMI or DMM and EMII sources for the PCCFA complexes. Two new 40Ar/39Ar ages (71.55 ± 0.49 Ma and 67.31 ± 0.78 Ma) are presented for the Tinguá and Itatiaia massifs, respectively. In addition, two new U-Pb ages (69.3 ± 2.2 Ma for Tinguá and 70.4 ± 2.6 Ma for Itatiaia) are presented along with a third U-Pb age of 65 ± 2 Ma obtained for Gatos Hill, which is the first published age for this massif. The compilation of geochronological data, along with these new ages, indicates that the decrease in ages from west to east is not regular. For example, the oldest age (Itatiaia – 90.5 Ma) and the youngest age (Tinguá – 39.1 Ma) are found in more central massifs of the magmatic alignment. This feature prevents the genesis of this alignment from being attributed to a conventional plume model. In this regard, the authors suggest the presence of a plume with widespread conduits that have used preexisting structures for the intrusion the alkaline rocks, a hypothesis supported by the orientation of these magmatic bodys (massifs and dikes).